Teacher Educator Reflections on Preparing First Year Pre-Service Teachers for School-Based Work Integrated Learning in An Online Learning Environment - Yolanda Nondumiso Mpu; Karin Hackmack; Irene Roy (Research in Social Sciences and Technology, 2022)
Due to the COVID 19 pandemic in 2020 and 2021, higher education institutions were forced to embark on online teaching and learning. This came at a point where the entire teacher fraternity was not prepared for this shift from traditional face-to-face interaction to virtual learning. This qualitative, exploratory study was undertaken as a comparative analysis of the teaching, learning and facilitation experiences of three Teacher Educators. The focus was on teacher educators who engaged in a formal online teacher training program with first year pre-service teachers enrolled on the Bachelor of Education qualification. Data was collected from the Teacher Educators in the form of interviews and reflective reports prepared at the conclusion of the 2021 academic year. The data was thematically analysed to distil common lessons, challenges and points for the 3 Teacher Educators with the intention of learning from and improving on practice. The paper addressed three research questions which guided the study and presents the researchers findings in the areas of student access to the learning platform; knowledge transfer from online lectures to practical application in the form of portfolio of evidence and the alignment between theory and practice. Recommendations include using a hybrid approach to preservice teacher preparation; using formative and summative assessment in making a judgement on competence and mastery and re-focussing student feedback as reflective essays.